THE ROLE AND REGULATION of MITOCHONDRIAL DYNAMICS IN CISPLATIN RESISTANCE IN HUMAN GYNECOLOGIC CANCER CELLS - Kong, Bao (Université d'Ottawa / University of Ottawa, 2015)
Cervical cancer (CECA) and ovarian cancer (OVCA) rank first and third in the number of new cases diagnosed among gynecologic cancers，and chemoresistance severely limits their treatment success. The underlying mechanism of chemoresistance is multi-factorial and partly due to defects in drug-induced apoptosis. Cisplatinum (CDDP) -induced, p53-mediated mitochondrial cell death is controlled by Akt and is a determinant of chemosensitivity in gynecologic cancer cells. Mitochondria dynamics (fusion and fission) are involved in the regulation of mitochondria-mediated apoptosis. The tumor suppressor prohibitin 1 (Phb1) is involved in long from Opa1 (L-Opa1) processing and p53-regulated apoptosis. Whether mitochondrial fusion protein Opa1 and its protease Oma1 as well as Phb1 are involved in the regulation of chemoresistance in CECA and OVCA cells are not known. The overall objective of my research is to increase the current understanding on the regulation of mitochondrial dynamics and on its role in chemoresistance in gynecologic cancer cells. We hypothesize that CDDP induces Phb1 binding to phosphorylated p53 (p-p53) and Bak, resulting in Bak activation and mitochondrial outer membrane permeabilization (MOMP). These responses also induce Oma1-mediated Opa1 processing, mitochondrial fragmentation and apoptosis but are inhibited by high Akt level in chemoresistant cells. Here we present evidence that CDDP induces Oma1 activation, L-Opa1 processing and mitochondrial fragmentation in chemosensitive but not in chemoresistant cells. Silencing p53 expression attenuated CDDP-induced L-Opa1 loss, mitochondrial fragmentation and apoptosis in chemosensitive cells, while reconstitution of p53 in p53-deficient (mutant or null) chemoresistant cells induced Oma1 activation, L-Opa1 processing and changes in mitochondrial dynamics irrespective of the presence of CDDP. In response to CDDP, p-p53 (ser15) dissociates Phb1 from Opa1-Phb1 complex and binds to Bak in chemosensitive but not chemoresistant cells. Inhibition of Akt is required for CDDP to induce L-Opa1 processing, mitochondrial fragmentation and apoptosis in chemoresistant cells. Our study suggests a mechanism that p53 regulates L-Opa1 processing and mitochondrial fragmentation in chemosensitive cells induced by CDDP, while this pathway is suppressed in chemoresistant cells. Dysregulated mitochondrial dynamics may in part be involved in the pathophysiology of CDDP resistance. Inhibiting Akt activity and inducing Opa1 processing may serve as novel therapeutic strategies for these gynecologic cancers.
Keywords: Cisplatin; Resistance